Fire-resistant construction panel and method for manufacturing fire-resistant construction panel
By integrating zonotrite, expandable perlite, and fibers into construction panels, the challenges of achieving high fire resistance, mechanical stability, low density, and ease of processing are addressed, resulting in panels suitable for diverse applications.
Patent Information
- Application Number
- JP2021563337
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-22
- Filing Date
- 2020-05-19
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2040-05-19
AI Technical Summary
Existing construction panels lack high fire resistance and mechanical stability, especially under prolonged high temperature loads, while also desiring low density and ease of mechanical processing.
The development of construction panels incorporating zonotrite, expandable perlite, and fibers, where zonotrite provides non-flammability and high mechanical stability, expandable perlite reduces density and enhances fire resistance, and fibers improve mechanical strength and processing ease.
The resulting construction panels exhibit high fire resistance, mechanical stability under prolonged high temperature exposure, low density, and ease of mechanical processing, making them suitable for various applications including drywall construction.
Smart Images

Figure 0007656545000001 
Figure 0007656545000002 
Figure 0007656545000003
Abstract
Description
[Technical field]
[0001] explanation The present invention relates to a highly fire-resistant construction panel and a method for producing a highly fire-resistant construction panel. [Background technology]
[0002] Construction panels are used in the construction of drywall. For example, construction panels are used as cladding elements in drywall construction, for example to cover walls or pipes. Construction panels are also used, for example, to create partition walls. In particular, construction panels are also used for the manufacture of ventilation ducts.
[0003] For fire safety reasons, there is also a regular need for highly fire-resistant construction panels, also known as fire panels.
[0004] Highly fire-resistant construction panels are known, for example, in the form of construction panels made from hydraulic setting cements, in particular hydraulic Portland cements, as well as aluminous or high aluminous cements.
[0005] Also, fire protection panels with high resistance to fire are also available in the form of calcium silicate panels, i.e. ternary CaO-SiO 2 -H 2 They are known in the form of construction panels based on at least one mineral phase in the O system. The mineral phases of this ternary system are usually also called CSH phases, and construction panels manufactured based on this phase are called CSH construction panels.
[0006] Ternary CaO-SiO 2 -H 2 In the O system, the phases CaO, SiO 2 , and H 2 There are many mineral phases that differ from each other in terms of their respective percentages of O. 。 Ternary CaO-SiO, on the basis of which construction panels are manufactured 2 -H 2Common mineral phases in the O system include, for example, the chemical formula Ca 5 S 6 O 17 5H 2 The mineral phase tobermorite has O.
[0007] However, many of the materials from which construction panels are routinely made do not provide the construction panels with a high level of fire resistance, since, for example, these materials would be destroyed or burned under uninterrupted high temperature loads.
[0008] However, in order to provide a high level of fire resistance, the construction panels must be able to withstand long, uninterrupted high temperature loads.
[0009] Furthermore, it is usually desired that the construction panel has the lowest possible density. Regardless of the low density, at the same time, it is usually desired that the panel has high mechanical stability, especially even under mechanical stress. At the same time, it is also desired that the construction panel can be easily processed mechanically, for example by drilling, stapling or sawing. Summary of the Invention [Problem to be solved by the invention]
[0010] The underlying object of the present invention is to provide a construction panel that is highly fire resistant.
[0011] It is a further object of the present invention to provide such a construction panel, which is highly fire resistant, that can also be made available at low densities.
[0012] A further object of the present invention is to provide such a highly fire-resistant construction panel, which has a high fire resistance that can be made available at a low density and at the same time a high mechanical stability even when subjected to long-term uninterrupted high-temperature loads.
[0013] A further object of the invention is to make available such a construction panel which has high fire resistance, which can be made available at low density, and at the same time high mechanical stability even when subjected to long-term uninterrupted high-temperature loads, which construction panel is also easy to process mechanically.
[0014] A further object of the invention is to provide a method for making such a construction panel available. [Means for solving the problem]
[0015] In order to be able to make such a construction panel available, according to the invention, a construction panel having high fire resistance and: Xonotlite, Expanded perlite, and Fiber, a construction panel comprising the same is made available.
[0016] The present invention is based on the surprising discovery that the above objects can be achieved by providing a highly fire resistant construction panel comprising xonotlite, expanded perlite, and fiber.
[0017] Xonotlite is a calcium silicate with hydroxide ions, or a ternary CaO-SiO 2 -H 2 It is a calcium silicate hydrate from the O system. The chemical formula for xonotlite is Ca 6 [Si 6 O 17 ](OH) 2 It is.
[0018] The advantage of xonotlite as a component in the construction panel of the invention is that it is not flammable and does not start to decompose until about 900 ° C. As a result, xonotlite confers a high level of fire resistance to the construction panel of the invention. At the same time, due to its high strength, xonotlite gives the construction panel a high mechanical stability. Another advantage of xonotlite is that this phase is not harmful to health. Therefore, it is also possible to use the construction panel of the invention indoors.
[0019] The construction panel of the present invention preferably contains xonotlite in a proportion of at least 20% by mass, more preferably in a proportion in the range of 20 to 50% by mass, and even more preferably in a proportion in the range of 20 to 40% by mass.
[0020] The information given in this specification in % by weight regarding the proportions by weight of the components of the inventive building panel is always based on the total weight of the inventive building panel, unless stated otherwise in individual cases.
[0021] The expanded perlite component has considerable advantages in the construction panels of the invention. For example, the proportion of expanded perlite in such construction panels allows construction panels with low density to be made available, since expanded perlite only has a low density or low bulk density. At the same time, the use of expanded perlite in construction panels allows construction panels with high mechanical stability at the same time, especially when subjected to long-term uninterrupted high-temperature loads, since expanded perlite is mechanically stable and highly fire-resistant. Furthermore, the panels can be used indoors, since expanded perlite is not harmful to health. Furthermore, the proportion of expanded perlite allows the construction panels to be mechanically easily processed.
[0022] In particular, however, according to the invention, it has surprisingly been found that expanded perlite is particularly advantageous for building panels for reasons arising from the manufacture of the building panels of the invention. For example, the open pore volume of the expanded perlite can be partially filled with xonotlite. This is because the components forming xonotlite (i.e. the components containing calcium oxide, the components containing silicon dioxide and water) penetrate into the open pore volume of the expanded perlite during the manufacture of the building panel and form xonotlite therein, and accordingly the open pores of the expanded perlite are at least partially filled with xonotlite. However, at least partially filling the open pores of the expanded perlite with xonotlite has proven to be advantageous for several reasons. For example, the absorbency of the expanded perlite is significantly reduced by the filling of the open mechanism with xonotlite, so that for any impregnation of the building panel, for example with a coating of paint or hydrophobizing agent, only a small amount of coating or hydrophobizing agent is necessary, since the expanded perlite mostly only superficially absorbs this substance. However, this may be particularly advantageous when such impregnation contains organic components that may impair the fire resistance of the construction panel. Furthermore, it has surprisingly been found that the mechanical stability of the expanded perlite is improved by the xonothlite being partially embedded in the open pores of the expanded perlite, which also improves the overall mechanical stability of the construction panel.
[0023] In this regard, one particularly preferred embodiment provides that the open pores of the expanded perlite are partially filled with xonotlite.
[0024] Surprisingly, it has been found according to the invention that the particle size of the expanded perlite in the building panel can be of particular importance for the mechanical stability of the building panel, even when exposed to fire. Thus, the mechanical stability of the building panel of the invention can be increased more and more if expanded perlite is increasingly present in the building panel with a particle size of up to 1.5 mm. In this respect, according to one particularly preferred embodiment, it is provided that the expanded perlite is predominantly or completely present with a particle size of up to 1.5 mm.
[0025] According to one preferred embodiment, it is provided that the expanded perlite is at least 50% by weight, more preferably at least 90% by weight, even more preferably 100% by weight, with a particle size of less than 1.5 mm. Furthermore, it can be preferably provided that the expanded perlite is at least 50% by weight, more preferably at least 90% by weight, even more preferably 100% by weight, with a particle size in the range of 0.01 to 1.5 mm. The information provided herein regarding the proportion by weight of expanded perlite in a particular particle size is in each case based on the total mass of expanded perlite in the building panel of the invention.
[0026] The particle size of the expanded perlite in the building panel can preferably be determined microscopically based on a polished section of the building panel, in particular using a microscopic analysis of the polished section, particularly preferably using an imaging computer-aided analysis program.
[0027] The construction panel of the present invention preferably contains expanded perlite in a proportion in the range of 8 to 20 mass %, more preferably in a proportion in the range of 10 to 15 mass %.
[0028] The mechanical strength of the construction panel of the invention can be further increased by using fibers, in which respect the construction panel forms a fiber-reinforced composite, the fibers being embedded in the matrix of the construction panel formed from xonotlite.
[0029] The construction panel of the present invention preferably contains fibers in a proportion in the range of 1.5 to 10 mass %, more preferably in the range of 2 to 8 mass %.
[0030] According to one particularly preferred embodiment, the fibers are in the form of at least one of the following types of fibers: organic fibers or inorganic fibers.
[0031] The organic fibers may preferably be in the form of at least one of the following types of fibers: cellulose fibers or carbon fibers. If the organic fibers are in the form of cellulose fibers, they may particularly preferably be in the form of kraft cellulose fibers.
[0032] The building panels preferably contain cellulose fibres, especially in the form of kraft cellulose fibres, in a proportion in the range 1-6% by weight, more preferably in the range 1-4% by weight.
[0033] The cellulose fibers, especially in the form of kraft cellulose fibers, preferably have at least one of the following shapes: an average fiber diameter in the range of 10 to 30 μm or an average fiber length in the range of 0.5 to 3 mm.
[0034] The inorganic fibers can preferably be in the form of glass fibers, particularly preferably the following: AES fibers, mineral fibers, basalt fibers, alumina fibers (Al 2 O 3 fiber), or silicate fiber (SiO 2 The fiber may be in the form of at least one of the following types of glass fibers:
[0035] According to one particularly preferred embodiment, it is provided that the glass fibres are in the form of AES fibres. As is well known, "AES fibres" (= alkaline earth silicate fibres) are made of the material system MgO-CaO-SiO 2AES fibers are particularly preferably of high purity, i.e., of the oxides MgO, CaO, and SiO, because the fibers thereby produce high refractoriness and withstand high application temperatures. 2 In addition, the proportion of other oxides is very small. One advantage of AES fibers in particular is that they are not classified as hazardous materials, in particular that they are not carcinogenic, so that the construction panel of the invention can be easily used indoors as long as it contains AES fibers. When the glass fibers are in the form of AES fibers, they preferably contain at least 60% by weight of SiO, more preferably a proportion in the range of 60-90% by weight, even more preferably a proportion in the range of 60-85% by weight, and even more preferably a proportion in the range of 70-85% by weight. 2 In addition, the AES fiber has a chemical composition comprising the above-mentioned SiO 2 According to one preferred embodiment, the AES fibers have a chemical composition comprising a proportion of MgO and CaO in the total mass in the range of 10-40% by mass, more preferably in a proportion in the range of 15-40% by mass, and even more preferably in a proportion in the range of 15-30% by mass, so long as they are SiO 2 It is provided that the AES fibers have a proportion of further chemicals in a proportion of less than 3% by weight, so long as they have the above-mentioned chemical proportions of MgO and CaO. The above information regarding the chemical composition of the AES fibers is based on the total mass of the glass fibers in the building panel of the invention.
[0036] The building panels according to the invention preferably contain glass fibres, in particular in the form of AES fibres, in a proportion ranging from 0.5 to 5% by weight, more preferably in a proportion ranging from 0.5 to 4% by weight.
[0037] The construction panel according to the invention preferably comprises glass fibres having a classification temperature according to DIN EN 1094-1:2008-09 of at least 1200° C., in particular having the abovementioned chemical composition.
[0038] The glass fibers preferably have an average fiber diameter in the range of 5 to 10 μm, more preferably in the range of 7 to 9 μm.
[0039] The AES fibers preferably have at least one of the following shapes: an average fiber diameter in the range of 5 to 15 μm (more preferably in the range of 7 to 9 μm) or an average fiber length in the range of 1 to 10 mm.
[0040] According to one particularly preferred embodiment, the fibers are in the form of AES fibers and kraft cellulose fibers.
[0041] In the building panels of the invention, the xonotlite forms the matrix in which the expanded perlite and fibers are embedded.
[0042] The expanded perlite and fibers are preferably uniformly distributed throughout the volume of the building panel of the present invention.
[0043] As mentioned above, highly fire-resistant construction panels, in particular so-called fire panels, in the form of cement-hardened panels based on hydraulic cements such as Portland cement and aluminous cements, in particular high aluminous cements, are known. However, according to the invention, it has been found that the fire resistance, in particular the mechanical strength of the construction panels of the invention, can also be deteriorated by such cements. In particular, these cements can also have a negative effect on the mechanical stability of the xonotlite when the construction panel is exposed to temperature loads. Therefore, according to one preferred embodiment, it is provided that the construction panels of the invention are free of cements, in particular Portland cement, aluminous cement and high aluminous cement, or contain only a small proportion of them.
[0044] The construction panel of the invention preferably comprises cement, in particular hydraulic cement, in particular Portland cement, aluminous cement and high aluminous cement only in a proportion of less than 10% by weight, more preferably in a proportion of less than 5% by weight and even more preferably in a proportion of less than 1% by weight.
[0045] According to one preferred embodiment, the construction panel of the invention comprises xonotlite, expanded perlite and fibres in a proportion of at least 33% by mass. It can further be preferably provided that the construction panel of the invention comprises xonotlite, expanded perlite and fibres in a proportion of up to 63% by mass. According to one preferred embodiment, the construction panel of the invention comprises xonotlite, expanded perlite and fibres in a proportion ranging from 33 to 63% by mass, more preferably in a proportion ranging from 35 to 55% by mass.
[0046] The building panels of the present invention may contain anhydrides as further components.
[0047] Such components in anhydrous form, i.e., CaSO 4 has the particular advantage that the xonotlite is stabilized by the anhydride, especially when the construction panel is subjected to temperature loads, in that the anhydride decomposes endothermically starting at a temperature of about 1180° C., so that the construction panel of the invention can be cooled, slowing down the decomposition of the xonotlite.
[0048] The construction panel of the invention preferably contains anhydrides in a proportion in the range of 0.5 to 5% by weight, more preferably in a proportion in the range of 0.8 to 2% by weight.
[0049] The building panels of the present invention may contain calcium carbonate as a further component.
[0050] Calcium carbonate, i.e., CaCO 3 may be present in the construction panels of the present invention in at least one of the mineralogical phases calcite, aragonite, or vaterite.
[0051] Like the anhydrides, calcium carbonate also has the advantage of stabilizing the xonotlite in the building panels, especially when subjected to temperature loads: since calcium carbonate starts to decompose endothermically from a temperature of about 825°C, the building panels can also be cooled, suppressing the decomposition of the xonotlite.
[0052] The construction panel of the invention preferably comprises calcium carbonate in a proportion ranging from 1 to 10% by weight, even more preferably in a proportion ranging from 1 to 5% by weight.
[0053] According to one preferred embodiment, the construction panel of the present invention is provided to contain xonotlite, expanded perlite, fibers, anhydrides, and calcium carbonate in a proportion of at least 35% by mass. Furthermore, it can be preferably provided that the construction panel of the present invention contains xonotlite, expanded perlite, fibers, anhydrides, and calcium carbonate in a proportion of up to 70% by mass. According to one preferred embodiment, the construction panel of the present invention is provided to contain xonotlite, expanded perlite, fibers, anhydrides, and calcium carbonate in a proportion in the range of 35 to 70% by mass, more preferably in the range of 37 to 57% by mass.
[0054] During the manufacture of the construction panels of the invention, further phases may be formed, in particular using the method of the invention described in more detail below. These further phases are in particular ternary CaO-SiO 2 phases not in the form of xonotlite. 2 -H 2 O-based phases (hereinafter referred to as "further CSH phases"). In particular, these further CSH phases may be the following phases: scotite (Ca 7 S 6 O 18 CO 3 (H 2 O) 2 ), tobermorite, or an X-ray amorphous calcium silicate phase (so-called "calcium silicate gel phase" or "CS gel phase").
[0055] In this respect, it can be preferably provided that the construction panel of the invention has such an additional CSH phase in a proportion of less than 65% by weight, in particular in a proportion in the range from 30 to 65% by weight, more preferably in a proportion in the range from 43 to 63% by weight.
[0056] The construction panel of the invention preferably comprises tobermorite in a proportion of up to 25% by weight, more preferably in a proportion in the range 10-25% by weight, even more preferably in a proportion in the range 10-20% by weight.
[0057] The construction panel of the present invention preferably contains scauthite in a proportion of up to 10% by mass, more preferably in a proportion in the range of 1 to 10% by mass, even more preferably in a proportion in the range of 1 to 8% by mass.
[0058] The construction panel of the present invention preferably contains an X-ray amorphous calcium silicate phase in a proportion in the range of 20 to 30% by mass.
[0059] According to one embodiment, it can be provided that the construction panel of the invention comprises xonotlite, expanded perlite, fibres, anhydrite, calcium carbonate and other CSH phases in a total mass of at least 92% by mass. According to one embodiment, it can be provided that the construction panel of the invention comprises xonotlite, expanded perlite, fibres, anhydrite, calcium carbonate and other CSH phases in a proportion ranging from 92 to 100% by mass, more preferably in a proportion ranging from 96 to 100% by mass.
[0060] The construction panel of the invention may contain a proportion of quartz, which may in particular result from the manufacture of the construction panel of the invention, in particular using the method of the invention described in more detail below. The construction panel of the invention preferably has a proportion of quartz of up to 10% by weight, more preferably in the range of 1-10% by weight, even more preferably in the range of 1-5% by weight.
[0061] The mineralogical composition of the panel is preferably determined by X-ray diffraction analysis, particularly preferably by the Rietveld method.
[0062] Regarding the chemical composition of the panel, the latter preferably contains 40-50% by mass, more preferably 42-48% by mass, of SiO 2 and a CaO content of 35 to 45 mass %, more preferably 36 to 43 mass %, and even more preferably 38 to 43 mass %.
[0063] The chemical composition of the panels is determined by X-ray fluorescence analysis in accordance with DIN EN ISO 12677. 2013-02.
[0064] In addition, the chemical composition of the panel may have a loss on ignition in a percentage ranging from 5 to 15% by mass. Loss on ignition may be caused in particular by water of crystallization and cellulose fibers in the construction panel.
[0065] The panel preferably contains less than 3% by weight, especially in the range of 1 to <3% by weight, of Al. 2 O 3 It has a chemical composition having a ratio of:
[0066] Furthermore, the panel preferably comprises Fe 2 O 3 , S.O. 3 , MgO, K 2 O, and Na 2 O are each present in a proportion of less than 1% by weight, where one, more, or all of these substances may be present in the building panel in such proportions of less than 1% by weight.
[0067] The panel is preferably made of SiO 2 and the proportion of CaO is at least 80% by mass, preferably in the range of 80 to 90% by mass of SiO 2 and CaO, and even more preferably, the proportion is in the range of 82 to 88 mass %.
[0068] Furthermore, regarding the chemical composition of the construction panels, CaO and SiO 2 The mass ratio is preferably less than 1.0, in particular in the range of 0.85 to <1.0.
[0069] Due to the expanded perlite in the construction panel of the invention, it is possible to provide the latter with a low density. The construction panel of the invention preferably has a maximum density of 900 kg / m 3 The density of the construction panel is particularly preferably between 400 and 900 kg / m 3 The density is determined after drying to constant weight at 105°C.
[0070] The construction panel of the present invention preferably has a thickness in the range of 10 to 60 mm.
[0071] Due to the high mechanical stability, especially given fire loads, the construction panels of the invention can be made available in long lengths. In this respect, the construction panels of the invention can have lengths of up to 2.5 m.
[0072] The structural panels of the invention can in particular be classified as "non-combustible A1" according to DIN EN 13501-1. 2010-01.
[0073] In particular, however, the construction panels of the invention can be made available with a high fire resistance, the panels remaining mechanically stable even when subjected to an especially uninterrupted fire load, in particular the construction panels of the invention have a mechanical stability of at least 90 minutes when exposed to fire according to the standard temperature curve according to DIN EN 1363-1:2012-10.
[0074] As explained below, the construction panel of the invention is preferably placed in an autoclave. After being placed in the autoclave, the construction panel can be provided with other components, such as impregnations (e.g. hydrophobizing agents or other coatings, etc.), laminations (e.g. metal laminations) or fasteners (e.g. clips, screw-in profiles, etc.). These additional components are not taken into account in the above information regarding the proportion by weight of the components of the construction panel in the total mass of the construction panel.
[0075] To manufacture a fire-resistant construction panel, according to the invention, the following steps are carried out: Providing a batch including: Ingredients containing calcium oxide, Ingredients containing silicon dioxide, Expanded Perlite, Fibers, and water, forming a batch; Applying pressure and temperature to the formed batch; Thereby, a method is provided that includes a step in which a calcium oxide containing component, a silicon dioxide containing component, and water form xonotlite.
[0076] The method of the present invention is particularly preferably used for producing the construction panels of the present invention described herein, so that the construction panels produced using the method of the present invention can particularly preferably have the characteristics of the construction panels of the present invention described herein.
[0077] The method of the present invention is based on the surprising discovery that it is possible to produce construction panels having the high fire resistance and properties of the construction panels of the present invention as described in more detail above by Hideaki Honma, provided in particular that these construction panels are formed from a batch comprising a calcium oxide-containing component, a silicon dioxide-containing component, expanded perlite, fibers, and water, which batch is formed and the formed batch is then subjected to pressure and temperature, whereby the calcium oxide-containing component and the silicon dioxide-containing component form xonotlite with the water.
[0078] Particularly surprising is the discovery by the present inventors that such construction panels can be produced having the advantageous properties described herein, so long as the batch contains expanded perlite.
[0079] The use of expanded perlite, on the one hand, has the considerable advantages mentioned above for the construction panels produced using this method, in particular the high strength, good fire resistance and excellent mechanical processability of the construction panels, at the same time as a reduction in the density of the construction panels.
[0080] In addition, however, the use of expanded perlite also has considerable advantages in the manufacture of construction panels. For example, it has been surprisingly found that in particular the high absorption capacity of expanded perlite, which the latter has due to its high open porosity, is very advantageous in the manufacture of construction panels. This is because, due to the high absorption capacity of expanded perlite, the water of the batch necessary for the formation of the xonotlite can be absorbed to a large extent by the expanded perlite and released again later on to the batch, in particular while the formed batch is loaded by pressure and temperature and thus the xonotlite is being formed. However, since the moisture of the batch is absorbed by the expanded perlite, batches with a high water content are easy to process and in particular cannot have a slurry-like consistency, but rather an earthy, wet consistency. However, due to this earthy, wet consistency of the batch, it is particularly easy to process the latter and also particularly easy to form the latter. In particular, there is no need to dry the batch before forming it.
[0081] In this respect, the process of the invention can in particular be carried out as a semi-dry process.
[0082] In order to be able to meet these advantageous properties during the manufacture of construction panels using the method of the invention, expanded perlite is preferably provided with a high open porosity, which preferably has a proportion of open porosity of more than 90% by mass, based on the total volume of the expanded perlite.
[0083] Furthermore, according to the invention, it has been found that expanded perlite fulfills the above mentioned advantageous functions during the manufacture of construction panels using the method of the invention, in particular if said expanded perlite has a particular particle size.
[0084] In this respect, according to one particularly preferred embodiment, it is provided that the expanded perlite has, predominantly or solely, a particle size of up to 1.5 mm.
[0085] According to one preferred embodiment, it is provided that the expanded perlite in the batch of the method of the invention is at least 50% by weight, more preferably at least 90% by weight, even more preferably 100% by weight, with a particle size of less than 1.5 mm. Furthermore, it can be preferably provided that the expanded perlite is at least 50% by weight, more preferably at least 90% by weight, even more preferably 100% by weight, with a particle size in the range of 0.01-1.5 mm. The information regarding the mass percentage of the expanded perlite at a particular particle size is based on the total mass of the expanded perlite in the batch. The particle size of the expanded perlite can be determined by sieving according to DIN EN 13055:2016-11.
[0086] The batches of the process of the invention preferably contain expanded perlite in a proportion ranging from 5 to 20% by weight, more preferably in a proportion ranging from 5 to 15% by weight.
[0087] The information given here regarding the percentages by mass of components of a batch is always based on the total mass of the batch, unless otherwise specified in a particular case.
[0088] According to the invention, when the method of the invention is carried out, the SiO in the total mass of the component containing calcium oxide and the component containing silicon dioxide is 2 In this respect, it is possible to form xonotlite together with water from a calcium oxide-containing component and a silicon dioxide-containing component, provided that the mass ratio of the chemical proportion of CaO to the chemical proportion of SiO (i.e. the so-called C / S ratio) is greater than 1.00, in particular greater than 1.00, in particular at most 1.20. In this respect, according to the invention, it is preferable to use a mass ratio of SiO to SiO in the total mass of the calcium oxide-containing component and the silicon dioxide-containing component in the inventive batch. 2 The mass ratio of the chemical proportion of CaO to the chemical proportion of SiO is preferably greater than 1.00, more preferably a maximum of 1.20, and particularly preferably in the range of 1.05 to 1.15.
[0089] A calcium oxide (CaO)-containing batch component may contain one or more substances containing calcium oxide. When a calcium oxide-containing component contains calcium oxide, the latter does not necessarily have to be in the form of calcium oxide. On the contrary, since calcium oxide is the only chemical component of a calcium oxide-containing component, calcium can also be present in a form other than that of an oxide, for example as a hydroxide.
[0090] According to one preferred embodiment, the calcium oxide-containing batch component is calcium hydroxide, i.e., Ca(OH) 2 According to one particularly preferred embodiment, the calcium oxide containing component is in the form of calcium hydroxide.
[0091] The batch preferably contains a component including calcium oxide in a proportion in the range of 30 to 40 mass %, more preferably in a proportion in the range of 32 to 38 mass %.
[0092] Silicon dioxide (SiO2 The ingredients of the batch containing ) can contain one or more substances containing silicon dioxide. If the silicon dioxide-containing ingredient contains silicon dioxide, it does not have to be in the form of silicon dioxide. On the contrary, silicon can be present in forms other than the oxide form, for example, as silicic acid, since silicon dioxide is the only chemical component of the silicon dioxide-containing ingredient.
[0093] According to one preferred embodiment, the silicon dioxide-containing batch component comprises quartz. According to one preferred embodiment, the silicon dioxide-containing component is in the form of quartz. This quartz is particularly preferably in the form of granules, particularly quartz powder. According to one preferred embodiment, the quartz or quartz powder is at least 95% by mass based on the total mass of quartz, and has a particle size of less than 200 μm, more preferably less than 160 μm.
[0094] The batch preferably contains a component comprising silicon dioxide in a proportion in the range of 17 to 27% by mass, more preferably in a proportion in the range of 20 to 25% by mass.
[0095] The batch preferably contains fibers in a proportion in the range of 1 to 10% by weight, more preferably in the range of 1.5 to 8% by weight.
[0096] According to one particularly preferred embodiment, the fibers are in the form of at least one of the following types of fibers: organic fibers or inorganic fibers.
[0097] The organic fibers may preferably be in the form of at least one of the following types of fibers: cellulose fibers or carbon fibers. If the organic fibers are in the form of cellulose fibers, they may particularly preferably be in the form of kraft cellulose fibers.
[0098] The batch preferably comprises cellulose fibres, in particular in the form of kraft cellulose fibres, in a proportion ranging from 0.5 to 6% by weight, more preferably from 1 to 4% by weight.
[0099] The cellulose fibers, especially in the form of kraft cellulose fibers, preferably have at least one of the following shapes: an average fiber diameter in the range of 10 to 30 μm or an average fiber length in the range of 0.5 to 3 mm.
[0100] The inorganic fibers can preferably be in the form of glass fibers, particularly preferably the following: AES fibers, mineral fibers, basalt fibers, alumina fibers (Al 2 O 3 fiber), or silicate fiber (SiO 2 The fiber may be in the form of at least one of the following types of glass fibers:
[0101] According to one particularly preferred embodiment, it is provided that the glass fibres are in the form of AES fibres, which can preferably have the properties of the AES fibres of the construction panel according to the invention.
[0102] The batch preferably contains glass fibres, especially in the form of AES fibres, in a proportion ranging from 0.5 to 5% by weight, more preferably in a proportion ranging from 0.5 to 4% by weight.
[0103] The batch preferably comprises glass fibres having a classification temperature according to DIN EN 1094-1:2008-09 of at least 1200° C., in particular having the abovementioned chemical composition.
[0104] The glass fibers preferably have an average fiber diameter in the range of 5 to 10 μm, more preferably in the range of 7 to 9 μm.
[0105] The AES fibers preferably have at least one of the following shapes: an average fiber diameter in the range of 5 to 15 μm (more preferably in the range of 7 to 9 μm) or an average fiber length in the range of 1 to 10 mm.
[0106] According to one particularly preferred embodiment, the fibers of the batch are in the form of AES fibers and kraft cellulose fibers.
[0107] The batch preferably contains water in a proportion in the range of 15 to 35% by mass, more preferably in a proportion in the range of 20 to 30% by mass.
[0108] The batch preferably comprises a calcium oxide-containing component, a silicon dioxide-containing component, expanded perlite, and fibers in a proportion of at least 95% by weight, more preferably at least 97% by weight, based on the dry weight of the batch, i.e., the total weight of the batch without water.
[0109] According to one preferred embodiment, the batch comprises at least 96% by weight, more preferably at least 97% by weight, of a calcium oxide-containing component, a silicon dioxide-containing component, expanded perlite, fibers, and water.
[0110] According to one preferred embodiment, the batch comprises anhydrite in a proportion ranging from 0.5 to 3% by weight, more preferably in a proportion ranging from 1 to 2% by weight.
[0111] According to one preferred embodiment, it is provided that the batch comprises a thickening agent. Such a thickening agent is an ingredient that thickens the batch to facilitate handling. According to one preferred embodiment, the thickening agent is present in the form of at least one of the following substances: methylcellulose, xanthan gum, guar or starch. The thickening agent is particularly preferably in the form of methylcellulose, particularly preferably in the form of modified methylhydroxyethylcellulose, in particular in the form of water-soluble, non-ionic, highly etherified methylhydroxyethylcellulose. The batch preferably comprises a thickening agent in a proportion ranging from 0.2 to 0.6% by weight.
[0112] According to one preferred embodiment, it is provided that the batch comprises a foaming agent. Such a foaming agent can be used to form bubbles or foam in the batch. As a result, the density of the batch and therefore of the building panels produced therefrom can be reduced. At the same time, such a foaming agent can be used to stabilize the batch. According to one preferred embodiment, the foaming agent is in the form of a surfactant. For example, the foaming agent can be present in the form of Sika® foaming agent SB 2 (trademark of Sika Deutschland GmbH). The batch preferably comprises a foaming agent in a proportion ranging from 0.05 to 0.25% by weight, more preferably in a proportion ranging from 0.05 to 0.1% by weight.
[0113] The batch of the method of the present invention preferably comprises at least 97% by weight, more preferably at least 99% by weight, and in some cases up to 100% by weight, of the calcium oxide comprising component, the silicon dioxide comprising component, the expanded perlite, the fibres, the anhydrite, the thickener and the foaming agent, and the water, so that the batch preferably comprises a proportion in the range of 97-100% by weight or more, preferably in the range of 99-100% by weight.
[0114] When the batch is formed, it takes the shape of a panel. The batch is preferably formed by pressing. Another advantage of the batch of the method of the present invention in particular is that the batch can be molded using a conventional press for forming construction panels, for example a press for forming cement construction panels or other construction panels for drywall. As mentioned above, the water in the batch is largely absorbed by the expanded perlite, so that the pressed panel proves to be mechanically very dimensionally stable. The batch is preferably pressed using a pressure in the range of 0.2 MPa to 0.32 MPA.
[0115] Another advantage of the fact that the water of the batch can be largely absorbed by the expanded perlite, as mentioned above, is that the water is not forced out of the batch when the latter is pressed.
[0116] The compression factor during pressing (i.e. the reduction in the volume of the batch during pressing) is preferably in the range of 2-3.
[0117] Before the batch is formed, the batch components can be mixed to distribute evenly throughout the batch volume.
[0118] The formed batch is subjected to pressure and temperature such that the calcium oxide containing component, the silicon dioxide containing component, and the water of the batch form xonotlite. Those skilled in the art also know the ambient conditions necessary to form xonotlite from these components of the batch using pressure and temperature, i.e., specifically the required pressure and the required temperature.
[0119] The batch in the autoclave is preferably subjected to pressure and temperature. Autoclaves according to the prior art, in particular industrial autoclaves, can preferably be used. For example, industrial autoclaves can be used, as are known, for example, for the production of sand-lime bricks.
[0120] When carrying out the process of the invention, the batch is preferably operated at a pressure in the range of 15 to 20 bar, more preferably at a pressure in the range of 16 to 18 bar. Pressure in this sense is overpressure, i.e. as long as it exceeds atmospheric air pressure at the location of the measured overpressure.
[0121] Furthermore, the batch is preferably subjected to a temperature, in particular at the pressures mentioned above, such that the saturated steam pressure is established. The temperatures required for this are known to the skilled person and can be determined, for example, using the steam pressure curve of water. In this respect, temperatures in the range of 200-220°C can be applied to the batch.
[0122] The batch is subjected to pressure and temperature for a period of time such that xonotlite is formed from the components of the batch. According to the invention it can be provided that the pressure and temperature are applied to the batch for a period in the range of 8 to 20 hours, in particular for a period in the range of 12 to 16 hours.
[0123] During the application of pressure and temperature, xonotlite is formed from the components of the batch. Additionally, during the application of pressure and temperature to the batch, additional materials may form from the batch, particularly additional calcium carbonate or additional CSH phases, depending on the composition of the batch and the pressure, temperature and length of time of such application.
[0124] In addition, the percentage of water in the batch can change while pressure and temperature are applied to the batch, which also leads to differences in the composition of the batch and the construction panel with respect to the percentage of the mass of each of some components, e.g., expanded perlite, fiber, or anhydrite.
[0125] The construction panel is obtained after the batch has been subjected to pressure and temperature or autoclaved, and can then be dried, for example, preferably to a residual moisture content in the range of 8 to 12% by weight, based on the total weight of the construction panel.
[0126] Furthermore, the construction panels obtained using the method of the present invention may have the characteristics of the construction panels of the present invention disclosed herein.
[0127] The subject of the invention also relates to the use of the construction panels of the invention in drywall, for example, provided that the construction panels are used to create partition walls, to create ducts for electrical wires, to create ventilation ducts, to create smoke extraction ducts, to cover beams, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0128] Further characteristics of the inventive construction panel and the inventive method arise from the claims and embodiments described hereinafter.
[0129] All the features of the invention can be combined with each other, individually or in combination, as required.
[0130] One embodiment of the present invention is described in more detail below.
[0131] Embodiment According to one embodiment of the method of the present invention, a batch was first made available containing components in the proportions by weight according to Table 1 below, each based on the total weight of the batch.
[0132] [Table 1]
[0133] The calcium oxide containing component was in the form of calcium hydroxide.
[0134] The silicon dioxide-containing component was in the form of quartz powder. The quartz powder was 95% by weight based on the total weight of the quartz powder and had a particle size of less than 50 μm. The quartz powder had a content of SiO 2 The chemical composition was 99% by mass.
[0135] The expanded perlite had 100% by mass of a particle size less than 1.5 mm and 98% by mass of a particle size less than 1.0 mm, based on the total mass of the expanded perlite. Additionally, the expanded perlite had a particle size of 0.03-1.0 mm, also 95% by mass based on the total mass of the expanded perlite.
[0136] The cellulose fibers were in the form of kraft cellulose fibers having an average fiber diameter of about 20 μm and an average fiber length of about 1.9 mm.
[0137] The AES glass fiber contains 75% by weight of SiO, based on the total weight of the AES glass fiber. 2 and 22 mass% CaO+MgO. The average fiber diameter was about 8 μm.
[0138] The foaming agent was in the form of a surfactant (Sika® Foaming Agent SB 2) and the thickener was in the form of modified methylhydroxyethylcellulose.
[0139] The total percentage of calcium hydroxide and quartz powder is based on the total mass of calcium hydroxide and quartz powder, SiO 2 The mass ratio of CaO to Al was 1.103.
[0140] The batch was mixed in a mixer and then pressed to produce fire panels at a pressure of 0.25 MPa in a commercial hydraulic press equipped with a punch to form a square panel with a side length of 1,250 mm and a thickness of 30 mm.
[0141] The pressed panels were then placed in an industrial autoclave at 18 bar pressure at the saturated vapour pressure and the temperature resulting therefrom (approximately 207° C.) for 12 hours.
[0142] Finally, the corresponding autoclaved panels were removed from the autoclave and dried in a drying cabinet to a residual moisture content of about 10% by weight.
[0143] The construction panel obtained thereafter was in the form of a highly fire-resistant construction panel according to the invention.
[0144] The construction panel was composed of the following components, each in a mass proportion based on the total mass of the construction panel, in accordance with Table 2 below:
[0145] [Table 2]
[0146] The mineralogical composition of the construction panels was determined by X-ray diffraction analysis using the Rietveld technique.
[0147] During microscopic examination of the construction panels, it was found that xonotlite had formed in the open pore volume of the expanded perlite, thereby causing significant closure of the open pores of the expanded perlite.
[0148] The chemical composition of the construction panels was determined by X-ray fluorescence analysis in accordance with DIN EN ISO 12676:2013-02. The construction panels then had substances in mass proportions according to Table 3 below, in each case based on the total mass of the construction panel.
[0149] [Table 3]
[0150] To determine the fire resistance, the fire behavior of the construction panels was carried out in the form of a beam cladding test (box test) without substructure, in which the panel parts were clamped, according to DIN EN 1363-1:2012-10. When the construction panels were then subjected to a temperature load according to the standard temperature curve according to DIN EN 1363-1:2012-10, the onset of sagging of the panels was determined only after 138 minutes, at a surface temperature of 1011 K. The panels therefore showed excellent fire resistance.
Claims
1. A highly fire-resistant construction panel, 1.1 Xonotlite and 1.2 Expanded perlite; 1.3 Fibers, The expanded perlite has a particle size of up to 1.5 mm and is present in an amount of at least 50% by weight, based on the total weight of the expanded perlite; The construction panel comprises the expanded perlite in a proportion ranging from 8 to 20% by mass.
2. 2. The construction panel of claim 1, comprising at least 33% by weight of the xonotlite, the expanded perlite, and the fibers.
3. 3. A construction panel according to claim 1 or 2, comprising said fibres in the form of at least one of the following fibres: glass fibres or cellulose fibres.
4. 4. A construction panel according to claim 3, comprising said glass fibres in the form of AES fibres.
5. The construction panel according to any one of claims 1 to 4, comprising the xonotlite in a proportion ranging from 20 to 50 mass%.
6. A construction panel described in any one of claims 1 to 5, containing the foamed perlite in a proportion ranging from 10 to 15 mass %.
7. A construction panel according to any one of claims 1 to 6, comprising said fibres in a proportion ranging from 1.5 to 10% by weight.
8. 4. The construction panel according to claim 3, comprising said cellulose fibers in a proportion ranging from 1 to 6% by mass.
9. 4. The construction panel according to claim 3, comprising said glass fibers in a proportion ranging from 0.5 to 5% by mass.
10. The construction panel according to any one of claims 1 to 9, comprising anhydrite.
11. A construction panel according to any one of the preceding claims, comprising calcium carbonate.
12. 1. A method for producing a fire resistant construction panel comprising the steps of: 13.1 Providing a batch comprising: 13.1.1 Components containing calcium oxide; 13.1.2 Components containing silicon dioxide; 13.1.3 Expanded perlite, 13.1.4 Fibers, and 13.1.5 Water; 13.2 forming the batch; 13.
3. A method comprising the step of applying pressure and temperature to the formed batch, whereby the calcium oxide comprising component, the silicon dioxide comprising component, and the water form xonotlite.
13. The batch comprises at least 50% by weight of the expanded perlite, based on the total weight of the expanded perlite, with a particle size of up to 1.5 mm; 13. The method of claim 12, wherein the batch comprises the expanded perlite in a proportion ranging from 5 to 20% by weight.
14. 14. The method according to claim 12 or 13, wherein the batch comprises the expanded perlite in a proportion ranging from 5 to 15% by weight.
Citation Information
Patent Citations
Expansive pearlite-hard cilicon calcium stone composite thermal insulating material and preparing process thereof
CN1559954A
Method of producing solid composition
JP1978009823A
Production of inorganic board
JP1997286643A
Production of calcium silicate-gypsum composition and formed product
JP1999171633A
Calcium silicate formed plate
JP2001226166A